Powers and prospects reflections on human nature and the social order - Chomsky, Noam 1928- (South End Press, 1996)
Eight essays, based on talks given during a week in Australia in 1995, bring together world-renowned linguist and outspoken critic of US foreign policy Chomsky's latest thinking. His topics encompass a wide scope from language and human nature, to the Middle East settlement, to the place of East Timor in the new world order.
Keywords: Anthropologie philosophique; Antropología filosófica; Internationale politiek; Philosophie du langage; Política mundial - 1989; Relations internationales - 1989-; Taal; Timor Timur; Internationale Politik; Philosophie; Sprache; Language and languages -- Philosophy; World politics -- 1989-; Philosophical anthropology; Menschenrecht; Ethnolinguistik; Weltpolitik; Sprachphilosophie; Weltordnung; Philosophische Anthropologie; Aufsatzsammlung